2009
DOI: 10.1371/journal.pone.0008288
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization and Phosphoregulation of the Francisella tularensis 1-Deoxy-D-Xylulose 5-Phosphate Reductoisomerase (MEP Synthase)

Abstract: Deliberate and natural outbreaks of infectious disease underscore the necessity of effective vaccines and antimicrobial/antiviral therapeutics. The prevalence of antibiotic resistant strains and the ease by which antibiotic resistant bacteria can be intentionally engineered further highlights the need for continued development of novel antibiotics against new bacterial targets. Isoprenes are a class of molecules fundamentally involved in a variety of crucial biological functions. Mammalian cells utilize the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…These initial results prompted additional experiments using a more focused set of compounds to probe the IspF cytidine and Zn 2+ binding sites, and yielded a ligand with low micromolar binding affinity. An additional study by Jawaid et al (2009) examined the IspF enzyme of F. tularensis. The enzyme was cloned and expressed in E. coli, the recombinant protein was then purified and enzymically characterized, and subsequent analysis showed that IspF is an excellent target for antibiotic development.…”
mentioning
confidence: 99%
“…These initial results prompted additional experiments using a more focused set of compounds to probe the IspF cytidine and Zn 2+ binding sites, and yielded a ligand with low micromolar binding affinity. An additional study by Jawaid et al (2009) examined the IspF enzyme of F. tularensis. The enzyme was cloned and expressed in E. coli, the recombinant protein was then purified and enzymically characterized, and subsequent analysis showed that IspF is an excellent target for antibiotic development.…”
mentioning
confidence: 99%
“…Fosmidomycin is a natural product produced by Streptomyces bacteria that inhibits DXR with K i values in the range of 10 –8 to 10 –7 M. 69 Although it is effective in the treatment of malaria caused by P. falciparum , 10,11 fosmidomycin, its acetyl analogue, and their phosphonate ester prodrugs are poorly active against M. tuberculosis . 12,13 Understanding the nature of interactions between fosmidomycin and DXR for the purposes of designing improved alternatives is therefore invaluable.…”
mentioning
confidence: 99%
“…Analysis of DXR from Francisella tularensis suggests that Ser177 (equivalent to Ser185 of E. coli DXR) is phosphorylated [27]. In view of the close proximity of Ser177 to the substrate binding site, phosphorylation of Ser177 could be related to DXR activity regulation.…”
Section: Mep Pathway Related Signaling and Regulationmentioning
confidence: 99%